Industrial training report: Rapid Bus Sdn Bhd (Rapid Penang) - Rosdi, Fareez Najwan (Universiti Teknologi MARA, Perlis, 2024)
This report is about my 6 months experience internship at Rapid Bus Sdn Bhd (Rapid Penang) at Georgetown, Pulau Pinang. Raudhah Penang is one of the subsidiary companies for Prasarana Berhad which specialize in providing transportation services in Malaysia. I have been assigned under Facility Management Admin Department with my supervisor which is as administrator (assistant vice president) at Rapid Penang, Puan Norhaida Binti Amir. I can say that it is such a wonderful journey and challenging journey for me where I cannot believe I can make it until my last day of internship. Since I am a Human Resources student, I did lots of work ad-hoc for HR and administration such as bills transaction, review lease and agreement, review ER for tender manage company’s assets and others. I can say that it is time consuming to adapt to this situation since the skills needed here is multitasking, I believe I already give my best for the company. To become an HR student is not easy same goes to carry HR and administration tasks. I have learnt a lot of things from the company which not only focused on HR and Administration. The political, economic, social, technical, environmental, and legal (PESTEL) aspects of the business are also included in this study, along with the company's strengths, weaknesses, opportunities, and threats (SWOT). I elaborated on what I had learned from the company's studies. The SWOT matrix I created along with my suggestions for how the organisation should advance is also provided. I have gained a great deal of advantages from this amazing adventure. My confidence to tackle my professional life in the future has grown as a result. Furthermore, it's a fantastic chance to learn new networking skills and work as a trainee in the administration department.